Molecular Recognition Characteristics of Cobalt(II)-Complex Molecularly Imprinted Polymer - Jigang, Jiang (Asian Journal of Chemistry, 2011)
Using Co-2,2'-dipyridyl complex as template, 4-vinylpyridine as the functional monomer and triallyl ioscyanurate as the cross-linking monomer, a cobalt(II)-complex template polymer was prepared by molecularly imprinting technology. The regulation effect of cobalt(II) to the selective recognition of polymer was studied. The results showed that the ability of selective recognition for 2,2'-dipyridyl by the polymer was distinctly enhanced in certain cobalt(II) acetate solution through equilibrium-binding experiment.